Efficiency and stability in subtropical beef cattle grazing systems in the northwest of Argentina - Nasca, Jose Andres; Feldkamp, C.R.; Arroquy, Jose Ignacio; Colombatto, Darío (2018)
The objective of this work was to evaluate the efficiency and stability of cow–calf, fattening and whole cycle beef cattle agro-ecosystems from the subtropical region of Argentina. For this purpose, an agro-ecosystem model consisting of a production and a management system was developed. Flexible management rules were incorporated. This simulation-based study compared potential trends of different agro-ecosystems under different animal body sizes and several management options traditionally applied in the region. The experiment aimed at estimating productive, energetic and economic efficiency and stability. The results showed that whole cycle and cow–calf systems were more stable but less productive than fattening systems. Within each agro-ecosystem, as body size increased, energetic and economic efficiency and stability decreased. Systems dynamics and multi-criteria approaches allowed recognizing tradeoffs among indicators, and main differences between agro-ecosystems. Further investigation is required to generalize these findings to other system structures, particularly when economic aspects are taken into account in decision making processes.